HOW TEACHERS ADAPT THEIR TEACHING APPROACHES TO DIFFERENT AGE GROUPS - Qodiraliyev Otabek (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
This article examines how teachers adapt their teaching approaches to meet the specific needs and characteristics of different age groups. It examines the importance of understanding the developmental stages, cognitive abilities, and learning styles of different age groups and how teachers modify their teaching strategies accordingly. The article discusses the different methodologies used by teachers, examines the implications and benefits of age-appropriate teaching, presents a discussion of the challenges teachers face, and provides an overview of the observed findings. The conclusion emphasizes the importance of appropriate teaching methods for optimal learning outcomes and suggests further areas for research. The article includes a bibliography for further reading.